2006
DOI: 10.1179/174313406x150104
|View full text |Cite
|
Sign up to set email alerts
|

Place of an Ultrasonography Simulator in Ultrasonography Training for Fertility Nurses

Abstract: Ultrasonography has a vital place in British fertility units, where it is commonly performed by nurses. This study evaluated the place of an ultrasonography simulator (Ultrasim) in ultrasonography training particularly for fertility nurses. Thirty-one participants took part in evaluation of the ultrasound simulator-two doctors, two ultrasonographers, and 27 fertility nurses and midwives with varying level of ultrasonography expertise. After using the simulator, participants were asked to give their opinion on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…Virtual reality training on ultrasound simulators is potentially beneficial in training, but there are few published studies. 10 A study in Germany has shown that training on an ultrasound VR simulator (SonoTrainer) can improve the accuracy of expertcertified scanners performing nuchal translucency measurements in the first trimester of pregnancy. Sophisticated VR software has since been added, thereby creating realistic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Virtual reality training on ultrasound simulators is potentially beneficial in training, but there are few published studies. 10 A study in Germany has shown that training on an ultrasound VR simulator (SonoTrainer) can improve the accuracy of expertcertified scanners performing nuchal translucency measurements in the first trimester of pregnancy. Sophisticated VR software has since been added, thereby creating realistic imaging.…”
Section: Discussionmentioning
confidence: 99%
“…Sonography is a subjective process, and the standard to which ultrasound is performed depends on the training and experience of the individual. Adequate training is essential before a sonographer is deemed competent to practice independently . Simulation training has been integrated into ultrasound learning as it can develop hand‐eye coordination and teach functionality of controls without the added stressor of the clinical setting .…”
Section: Resultsmentioning
confidence: 99%
“…Adequate training is essential before a sonographer is deemed competent to practice independently . Simulation training has been integrated into ultrasound learning as it can develop hand‐eye coordination and teach functionality of controls without the added stressor of the clinical setting . This is important especially when it comes to teaching intimate ultrasound examinations .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations